Left ventricular noncompaction cardiomyopathy with apical septal ventricular tachycardia - Debasish Das; Debasis Acharya; Tutan Das; Jogendra Singh; Sashikant Singh; Subhas Pramanik (Heart India, 2021)
We present a rare case of left ventricular noncompaction (LVNC) in a 23-year-old female with recurrent syncope with electrocardiography documentation of apical septal ventricular tachycardia (VT). Abnormal embryological myocardial maturation presenting as LVNC with electrogenic heterogenity across the noncompacted spongiform segments result in recurrent VT and mandates automated intracardiac defibrillator implantation (AICD). These subsets of patients in spite of AICD implantation require life-long broad-spectrum antiarrythmic in the form of amiodarone and beta-blocker to prevent a crisis of VT storm or sudden cardiac death.